(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background: Post stroke pneumonia is a major cause of mortality and morbidity in patients with stroke fed via Nasogastric Tubes (NGT). Metoclopromide, a prokinetic agent, has been recommended to reduce incidence of aspiration pneumonia, but its efficacy is controversial. The aim of the study was to assess whether regular treatment with Metoclopromide could safely reduce the rate of aspiration pneumonia in stroke patients fed by NGT. Materials and methods: This double blind randomized placebo-controlled trial was carried out in Department of Neurology, Chittagong Medical College Hospital, during September 2017 to August 2018. One hundred consecutive patients admitted in Neurology ward with no signs of pneumonia within 7 days of stroke onset and 48 hours of insertion of a NGT were recruited. Consecutive eligible patients were randomly allocated to receive either Metoclopromide 10 mg or placebo thrice daily via NGT for maximum 7 days or until NG feeds were discontinued whichever was earlier. Clinical signs of aspiration pneumonia were recorded daily. On 21st day after recruitment patients’ health and the level of recovery was reviewed by Modified Rankin Scale (MRS) and recorded. Results: One hundred patients [Mean age, 60.88 (±13.99) years, 36 men and 64 women] were randomized in a 1:1 ratio. Both the groups were similar in terms of baseline characteristics. Patients treated with Metoclopromide was 3.71 times more likely have no pneumonic episodes during their 7 days of treatment compared to placebo group. Regarding number of aspiration episodes 3.16 times more aspiration were noticed in placebo group compared to Metoclopromide group. The adjusted mean differences of number of antibiotic days and MRS score at day 21 were also significantly more in placebo group than Metoclopromide group. However, mortality at 21 days was similar in two groups. Diarrhoea was the only observed adverse event with similar distribution in both groups. Conclusion: This study confirmed that Metoclopromide may reduce the risk of aspiration pneumonia in stroke patients receiving nasogastric tube feeds. JCMCTA 2020 ; 31 (2) : 82-88